1333 Tio2 and tio2-mesoporous silica nanoparticle toxicity evaluated on primary human peripheral blood mono/lymphocytes. (24th April 2018) - Petrarca, C; Clemente, E; Zaccariello, G; Sabbioni, E; Di Gioacchino, M
Abstract : Introduction: TiO2 -NPs are the most produced nanomaterial as UV filters. They are considered as nontoxic at the exposure levels of the occupational environments; nevertheless, potentially dangerous organic molecules can be formed due to photocatalysis. Mesoprous silica (SiO2 ) nanoparticles (MSN) incorporating Ti-nano were produced to improve their properties. We studied whether human lymphocytes/monocytes can be the target of a toxic action of all these NPs. Methods: Activated/quiescent huPBMCs were exposed ex-vivo to: TiO2 -NPs (21 nm); MSN (100 nm); TiO2 -MSN (4.4 nm TiO2 into MSN pores). They were characterised for: cell viability/apoptosis by MTT and Annexin-V; ROS by DCFH oxidation; nuclear morphology by fluorescence microscopy; cytokines by ELISA. Results: The viability of activated lymphocytes exposed to the highest doses all NPs was significantly reduced. All NPs induced apoptosis, but only TiO2 -NPs induced ROS. IL-2, IL-17, IFN-g were downmodulated by all; MSNs were associated with increased IL-1β and IL-4 secretion; TiO2 -NPs induced IL-10, TNF-α and IL-23. Conclusion: Different patterns of cytokine in response to the three different NPs tested: they are all immunosuppressive, but only TiO2 -MSN seem to act as pro-inflammatory and pro-allergic agents. The presence of TiO2 in MSN appear to influence the effects of these larger NPs, possibly related to its pro-oxidative and pro-apoptotic effect.